Measured values of Ba/Ca in coral and coralline algae for seawater barium calibrations - Williams, Thomas J; Standish, Christopher D; Archambault, Philippe; Godbold, Jasmin A; Solan, Martin; Katsamenis, Orestis; Basford, Philip; Foster, Gavin L (In: Williams, TJ et al. (2023): A global database of measured values of Li/Mg, Mg/Ca, Sr/Ca, Ba/Ca, U/Ca and Sr-U for coral and coralline algae paleoenvironment calibrations [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.962897, 2023)
A comprehensive georeferenced database of measured values of Ba/Ca in coral and coralline algae compiled from the scientific literature (1950-2021; http://www.webofknowledge.com, accessed 2022-09-30).
Keywords: aragonite; Ba/Ca; coralline algae; Corals; high-Mg calcitic corals; Li/Mg; Mg/Ca; octocorals; paleotemperature proxy; seawater barium; Sr/Ca; Sr-U; U/Ca